मध्यप्रदेश का लोकनाट्य : माच - Shivkumar 'Madhur' (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2000)
Mach is a folk drama in the tribal region of Madhya Pradesh. The dramatist focused on the various steps , techniques and importance of folk drama.
Madhyapradesh ka Lok Natya : Mach
Keywords: मध्यप्रदेश का लोकनाट्य : माच; Madhyapradesh ka Lok Natya : Mach; Folk Drama; Hindi; Hindi